Community based water management: challenges and opportunities - Shirin G. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The present account is based on a seven weeks' ethnographic fieldwork in Faisalabad Irrigation zone in Punjab Pakistan, conducted as part of degree requirement for MSc. in Anthropology and Ecology of Development at University College London. The focus of the study is on the introduction of 'Farmer Organization' on the Dabbanwala distributary as part of a three-tiered devolution plan under the 'institutional reforms' component of the National Drainage Program (NDP). Due to the nature of the study, which was ethnographic, the Farmer Organization was not studied in isolation but as part of the larger cultural milieu.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)